A 7-month inhalation toxicology study in C57BL/6 mice demonstrates reduced pulmonary inflammation and emphysematous changes following smoking cessation or switching to e-vapor products. (11th March 2021) - Kumar, Ashutosh; Kogel, Ulrike; Talikka, Marja; Merg, Celine; Guedj, Emmanuel; Xiang, Yang; Kondylis, Athanasios; Titz, Bjoern; Ivanov, Nikolai V; Hoeng, Julia; Peitsch, Manuel; Allen, Joshua; et al.
Cigarette smoking causes serious diseases, including lung cancer, atherosclerotic coronary artery disease, peripheral vascular disease, chronic bronchitis, and emphysema. While cessation remains the most effective approach to minimize smoking-related disease, alternative non-combustible tobacco-derived nicotine-containing products may reduce disease risks among those unable or unwilling to quit. E-vapor aerosols typically contain significantly lower levels of smoke-related harmful and potentially harmful constituents; however, health risks of long-term inhalation exposures are unknown. We designed a 7-month inhalation study in C57BL/6 mice to evaluate long-term respiratory toxicity of e-vapor aerosols compared to cigarette smoke and to assess the impact of smoking cessation (Cessation group) or switching to an e-vapor product (Switching group) after 3 months of exposure to 3R4F cigarette smoke (CS). There were no significant changes in in-life observations (body weights, clinical signs) in e-vapor groups compared to the Sham Control. The 3R4F CS group showed reduced respiratory function during exposure and had lower body weight and showed transient signs of distress post-exposure. Following 7 months of exposure, e-vapor aerosols resulted in no or minimal increase in pulmonary inflammation, while exposure to 3R4F CS led to impairment of lung function and caused marked lung inflammation and emphysematous changes. Biological changes observed in the Switching group were similar to the Cessation group. 3R4F CS exposure dysregulated the lung and nasal tissue transcriptome, while these molecular effects were substantially lower in the e-vapor group. Results from this study demonstrate that in comparison with 3R4F CS, e-vapor aerosols induce substantially lower biological responses including pulmonary inflammation and emphysematous changes, and that complete switching from CS to e-vapor products significantly reduces biological changes associated with CS in C57BL/6 mice.